PENGARUH DIGITAL MARKETING DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNAAN APLIKASI POSPAY DI BANGKALAN - Syaiful Rizal; Ika Lis Mariatun; Yusrianto Sholeh (JURNAL ILMIAH EDUNOMIKA, 2023)
PT Pos Indonesia (Persero) made a change, namely in terms of the use of information technology. The digital transformation currently being carried out by the post office is by creating a product in the form of the Pospay application. The Bangkalan Post Office currently also accepts payment services through the Pospay application, so this makes it easy for Bangkalan people to make payments. The purpose of this study was to determine the effect of digital marketing and service quality on the decision to use the Pospay application. Analysis of the data used in this study using simple regression analysis. The results of this study indicate an R square value of 0.791 which can be interpreted that Digital Marching and Service Quality have an influence of 79.1% on the decision to use. The results of the regression analysis show that the value of the variable X1 (Digital Marketing) is 0.508 and the value of the variable X2 (Quality of Service) is 6.288. Thus it can be said that the positive constant value shows the positive influence of the independent variables, namely Digital Marketing and Service Quality. The results of the partial t test show that digital marketing and service quality partially affect usage decisions with a significance value of 0.000. While the results of the simultaneous F test show that Digital Marketing and Service Quality simultaneously influence the Decision to Use with a calculated F value = 105.822 with a significance level of 0.000.